2015
DOI: 10.1016/j.fgb.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of seven species in the Cryptococcus gattii/Cryptococcus neoformans species complex

Abstract: Phylogenetic analysis of 11 genetic loci and results from many genotyping studies revealed significant genetic diversity with the pathogenic Cryptococcus gattii/Cryptococcus neoformans species complex. Genealogical concordance, coalescence-based, and species tree approaches supported the presence of distinct and concordant lineages within the complex. Consequently, we propose to recognize the current C. neoformans var. grubii and C. neoformans var. neoformans as separate species, and five species within C. gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
581
1
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(609 citation statements)
references
References 322 publications
6
581
1
21
Order By: Relevance
“…Table 2 lists proposals for revisions to names associated with fungi of medical importance published between 2012 and 2015. The most controversial of these is the proposal to reorganize the Cryptococcus gattii-C. neoformans species complex into seven new species, two derived from C. neoformans and five from within C. gattii (16). This proposal is based on data from numerous phylogenetic analyses (including whole-genome analyses) and genotyping studies that have revealed significant genetic diversity within the species complex.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 lists proposals for revisions to names associated with fungi of medical importance published between 2012 and 2015. The most controversial of these is the proposal to reorganize the Cryptococcus gattii-C. neoformans species complex into seven new species, two derived from C. neoformans and five from within C. gattii (16). This proposal is based on data from numerous phylogenetic analyses (including whole-genome analyses) and genotyping studies that have revealed significant genetic diversity within the species complex.…”
Section: Resultsmentioning
confidence: 99%
“…grubii AFLP1/VNI Â C. gattii AFLP4/VGI (serotype AB, genotype AFLP9) and C. neoformans var. grubii AFLP1/VNI Â C. gattii AFLP6/VGII (serotype AB, genotype AFLP11) (Meyer et al, 2009;Trilles et al, 2012;Cogliati et al, 2013;Kaocharoen et al, 2013;Hagen et al, 2015). These major molecular types have subsequently been confirmed using RFLP analysis of the orotidine monophosphate pyrophosphorylase (URA5) or phospholipase B (PLB1) genes, amplified fragment-length polymorphism (AFLP) and multi-locus sequence typing (MLST) analysis.…”
Section: Introductionmentioning
confidence: 98%
“…The global incidence varies from 0.04 to 12 % and accounts for 13-40 % of the annual death rate among HIV-infected patients in areas of sub-Saharan Africa (Park et al, 2009). The fungal agent involved in the disease is the C. neoformans/Cryptococcus gattii species complex, belonging to the phylum Basidiomycota and subdivided into seven haploid and four hybrid genotypes (Trilles et al, 2008;Meyer et al, 2009;Cogliati et al, 2013;Hagen et al, 2015). C. neoformans var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the ambiguities based on nonmolecular methods were caused by morphological diversity associated with different developmental stages of the same fungus (Singer 1986;Kurtzman et al 1998;O'Donnell 2000). On the other hand, multiple cryptic species are often found within previously described single morphological or physiological species, even for some "well-studied" species complexes (e.g., O'Donnell et al 2004;Short et al 2013;Hagen et al 2015). Furthermore, globally, the number of traditional taxonomists, including fungal taxonomists, is on the decline (Drew 2011).…”
Section: Introductionmentioning
confidence: 99%